Ayuntamiento de Madrid en "Madrid en Vanguardia". - Gallardo, Juan A. Barranco (Madrid : Ayuntamiento de Madrid, 1987)
Araguren, Paloma ; Baschet, Bernard & François ; Carmenzim, José ; Chia, Sandro ; Garcia, Conchi ; Garcia, Jorge ; Gomez, Maria José ; Harras, Machu ; Herencia, Alberto ; Leonard, Santiago ; Llorente, Francisco Garcia ; Mayo, Luis ; Merz, Mario ; Salcedo, José Luis ; Tatafiore, Ernesto ; Vedova, Emilio
Spaans
boek
Keywords: Madrid